Backup Pattern for traction system of FWIA electric vehicle to guarantee maneuverability and stability in presence of motor faults and failures - Liang, Zhongchao; Wang, Zhongnan; Duan, Jianghua; Liu, Jian; Wong, Pak Kin; Zhao, Jing (Journal of the Franklin Institute, 2024)
Faults and failures in driving motors of four-wheel-independently-actuated (FWIA) electric vehicles can lead to hazardous accidents. To address this challenge, this paper introduces a novel “Backup Pattern” by grouping the driving motors into front and rear traction subsystems. This “Backup Pattern” ensures the optimal allocation of driving torque between functional motors, providing a reliable and effective mechanism to mitigate the impact of faulty motors on the vehicle’s overall performance. Based on the torque distribution strategy, a composite controller structure is presented, utilizing the second-order sliding mode algorithm to design both the traction controllers for longitudinal and differential torques and an active-front-steering (AFS) controller for additional steering angle. The composite controller not only enhances the vehicle’s maneuverability and stability but also copes with uncertainties and disturbances in the vehicle system. Hardware-in-loop (HiL) tests validate the superior effectiveness and robustness of the designed controller, showcasing its ability to enhance FWIA electric vehicle performance compared to the conventional first-order sliding mode control-based method.